Nurturing Job Satisfaction: Social Interactions and Work Environment via Empowering Motivation - Karsim, Karsim; Susilowati, Ervan; Setiawan, Wahdan Budi; Syafii, Mochamad; Rijal, Syamsu (SAFE-Network, 2023)
This study examined the role of social interactions, the work environment, and work motivation in influencing job satisfaction among employees at the Sekretariat Daerah Pontianak. The findings revealed significant relationships and provided insights into the dynamics of these variables. The results indicated that social interactions had a direct and significant impact on job satisfaction. Positive interactions, such as effective communication and collaboration, enhanced job satisfaction levels. Similarly, the work environment was found to influence job satisfaction, with factors such as physical conditions, organizational culture, and leadership practices playing a significant role. Work motivation was identified as another crucial factor affecting job satisfaction. Employees who were motivated and engaged in their work reported higher levels of job satisfaction. However, the study found that work motivation did not fully mediate the relationships between social interactions, the work environment, and job satisfaction. Based on these findings, it is recommended that the Sekretariat Daerah Pontianak prioritize fostering positive social interactions, improving the work environment, and promoting work motivation as separate but interconnected factors in enhancing job satisfaction. The study provides valuable insights for organizational leaders and policymakers to understand the factors influencing job satisfaction. By addressing social interactions, the work environment, and work motivation, the organization can create a more satisfying work experience and ultimately improve employee well-being and performance.